Ruskin Bond's desh : celebrating root and defining identity - Pal, Arup (New Delhi Bloomsbury, 2020)
This book explores the dilemma of Bond's 'two selves' and his existential search for an identity. This exploration, analysed across six chapters, is informed by a variety of postcolonial, historical, informational and critical texts on Bond and Anglo-Indians. Arup Pal focuses on four key literary works of Bond-The Room on the Roof, A Flight of Pigeons, Scenes from a Writer's Life and A Handful of Nuts-from the perspective of the author's developing sense of personal, national and cultural identity. He traces the journey that the author and his protagonists embark on in order to seek and ultimately define their sense of being.
Keywords: Identity (Psychology) in literature